Bacteria-Based Self-Healing Concrete Technologies: A Review of Literature and Future Perspectives - Gaidhane, Rohit N.; Shende, Tushar G.; Rai, Alok (International Journal on Theoretical and Applied Research in Mechanical Engineering, 2025)
The purpose of this literature review is to analyses various work conducted on concrete that heals itself formed by incorporation of bacteria. Self-healing concrete utilizing bacteria is a noteworthy development in the field of sustainable construction technology. This literature review synthesizes findings from a range of recent studies on the mechanisms, performance, and challenges of bacteria-based self-healing concrete systems. Research indicates that incorporating specific bacterial strains predominantly from the Bacillus genus into concrete enables the material to autonomously repair cracks through the Calcium carbonate precipitation caused by microbes, which efficiently seals fractures and restores integrity. Multiple papers demonstrate enhancements in mechanical properties, such as compressive strength and durability, along with the ability to heal cracks under various environmental conditions. Key factors influencing self-healing performance include the choice of bacterial species, nutrient availability, crack size, and the highly alkaline environment of concrete; advances in encapsulation methods and genetic engineering further enhance bacterial viability and healing efficiency. Despite demonstrated benefits, challenges remain in optimizing economic feasibility, ensuring long-term viability of bacteria, and scaling the technology for widespread application. Collectively, the reviewed literature highlights bacteria-powered self-healing concrete as a promising, environmentally aligned material poised to transform the maintenance and resilience of infrastructure.